The automotive industry in Nigeria: problems and prospects (2003)
Serious national efforts towards the development of the automotive industry in Nigeria took place in the early 1970s, with initial joint venture agreement between Peugeot and Volkswagen companies. By 2001, there were over 20 different enterprises manufacturing different types of vehicles, from boats to trucks, including motorcycles and bicycles and automobiles established in Nigeria. The capacity utilization of the majority of these companies, however, very low, largely due to the high cost of importing the components needed to assemble vehicles. The authors suggest that government policy should promote the development of a wholly made-in- Nigeria automobile, and that this would in turn stimulate the establishment of ancillary companies to supply the necessary components.